REDUCING THE BOOSTER STATIONS ENERGY CONSUMPTION BY WAY OF ELIMINATING OVERPRESSURE IN THE WATER SUPPLY NETWORK - G. N. Zdor; A. V. Sinitsyn (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The energy efficiency improvement of the city housing-and-utilities infrastructure and watersupply and water-disposal systems poses an occurrent problem. The water-supply systems energy consumption sizable share falls on the pump plants. The article deals with the issues of the operating regime management of the existing booster stations equipped with a group of pumping units regulated with frequency converters. One of the optimization directions of their energy consumption is the reduction of over-pressure in the water-distribution network and its sustentation within the regulatory values. The authors offer the structure and methodology of the data collection-and-analysis automated system utilization for revealing and eliminating the overpressure in the water-supply network. This system is designed for the group management of booster-stations operating regimes on the ground of data obtained from the pressure controlling devices at the consumers. The data exchange in the system is realized via GSM.The paper presents results of the tests carried out at the booster stations in some major cities of the Republic of Belarus. The authors analyze dependence of overpressure in the network on the methods of the plant output pressure sustentation (daily graph or constant pressure). The authors study the elimination effect of over-pressure in the water distribution network on changing the booster station pumping units operation regimes. The study shows that eliminating over pressure in the water distributing network leads to lowering the booster station pressure. This in its turn decreases its energy consumption by 15–20 % depending on the over pressure fixed level.